MoS2 Nanosheets Vertically Aligned on Hierarchically Porous Graphitic Carbon for High-Performance Lithium Storage. Issue 11 (1st January 2018) - Sun, Dongfei; Miao, Xuan; Yang, Juan; Li, Haiqiang; Zhou, Xiaozhong; Lei, Ziqiang
Abstract : Molybdenum disulfide (MoS2 ) is considered as a promising anode for next-generation Lithium-ion batteries (LIBs) due to its high theoretical capacity (∼ 670 mAh g −1 ). However, its low conductivity and enormous volume expansion during charge/discharge processes lead to a poor cycling stability and inferior rate performance. To address these issues, MoS2 nanosheets @ hierarchically porous graphitic carbon composite is designed and prepared by a metal compound-assisted chemical vapor deposition method combined with the hydrothermal method. The as-prepared MoS2 nanosheets @ hierarchically porous graphitic carbon composite exhibits a high reversible capacity of 1027 mAh g −1 at 0.1 A g −1, a good rate capability of 857 mAh g −1 at 1 A g −1, and an excellent cycling stability (792 mAh g −1 after 500 cycles at 1 A g −1 ). The outstanding performance can be attributed to the unique 3D structure of the MoS2 nanosheets @ hierarchically porous graphitic carbon composite, which not only provide more active sites and facilitate the access of ions, but also improve the conductivity and effectively suppress the volume change during the charge/discharge process.